Horsford-Tryon families papers
Chiefly correspondence of Horsford and Tryon family members primarily in central New York.
Correspondence of Jerediah Horsford and his wife, Maria Charity Norton Horsford, relating to his service as U.S. representative from New York, the Whig party, Free Soil Party, the death of Henry Clay, antislavery politics, and social and political life in Washington, D.C. Subjects also include boardinghouse life, slavery in Washington, D.C., and Myrtilla Miner and her school, the Normal School for Colored Girls in Washington, D.C.
Correspondence of Eben Horsford pertains to his years as a student at Rensselaer Polytechnic Institute; his appointment to the faculty of Harvard College in 1847 and life in Cambridge, Mass.; his commitment to women's education; Emma Willard, and her school, the Troy Female Seminary; and daguerreotypes.
Correspondence of Eliza Horsford Tyron concerns her student years at Miss Bennet's School in Auburn, N.Y., and the Le Roy Female Seminary, Le Roy, N.Y.; domestic life, courtship, marriage, and childbirth; life in Rochester, N.Y.; political events of the Whig Party; and a visit by Jenny Lind to Rochester in 1850. Correspondence of Eliza's husband and banker, James Tryon pertains chiefly to banking and commerce in New York, Hartford, Conn., and along the Erie Canal. Includes correspondence with Eliza's cousin, Harriet Hinsdale Haskell, and James's friend, James Richards Cox.
Subjects also include farming in upstate New York, medical matters, and travel plans and descriptions of trips in New York, Connecticut, Washington, D.C., and Cambridge, Mass. Correspondents include Henry Clay, Stephen Decatur, and William Gillette.
Typewritten transcripts, in part.
Members of the Horsford (Hosford) and Tryon families. Family members represented include Jerediah Horsford, U.S. representative from New York (1851-1853), missionary to the Seneca Indians in Moscow, N.Y., and farmer; his wife, Maria Charity Norton Horsford; and their children: Eben Norton Horsford, chemist and advocate for women's education; Julia Horsford Norton; Laura Horsford; Maria Horsford Byam; and Eliza Horsford Tryon and her husband, James Tryon, banker.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Originally cataloged as the Charry Maria Norton Horsford papers, 1851-1853. Correct name is Maria Charity Norton Horsford.
Keywords: Byam, Maria Horsford, -- 1826- -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Clay, Henry, -- 1777-1852 -- Death and burial; Cox, James Richards -- Correspondence; Decatur, Stephen, -- 1779-1820 -- Correspondence; Gillette, William, -- 1853-1937 -- Correspondence; Haskell, Harriet Hinsdale -- Correspondence; Horsford, Eben Norton, -- 1818-1893 -- Correspondence; Horsford, Jerediah, -- 1791-1875 -- Correspondence; Horsford, Laura, -- 1828- -- Correspondence; Horsford, Maria Charity Norton, -- 1790-1859 -- Correspondence; Lind, Jenny, -- 1820-1887.; Miner, Myrtilla, -- 1815-1864.; Norton, Julia Horsford, -- 1822- -- Correspondence; Tryon, Eliza Horsford, -- 1820-1883 -- Correspondence; Tryon, James, -- 1820-1895 -- Correspondence; Willard, Emma, -- 1787-1870.; Hosford family; Tryon family; Free Soil Party (U.S.); Harvard College (1780- ); Le Roy Female Seminary; Miss Bennet's School (Auburn, N.Y.); Normal School for Colored Girls (Washington, D.C.); Rensselaer Polytechnic Institute; Troy Female Seminary; Whig Party (U.S.); African Americans -- Education -- Washington (D.C.); African Americans -- Washington (D.C.); Agriculture -- New York (State); Banks and banking -- Connecticut -- Hartford; Banks and banking -- New York (State); Boardinghouses -- Washington (D.C.); Childbirth -- New York (State); Courtship -- New York (State); Daguerreotype; Education -- Washington (D.C.); Medicine -- New York (State); Slavery -- United States; Slavery -- Washington (D.C.); Women -- Education; Women -- Education -- New York (State); Women -- Education -- United States; Cambridge (Mass.) -- Description and travel; Cambridge (Mass.) -- Social life and customs; Connecticut -- Commerce; Connecticut -- Description and travel; Erie Canal (N.Y.) -- Commerce; Hartford (Conn.) -- Commerce; Massachusetts -- Social life and customs; New York (State) -- Commerce; New York (State) -- Description and travel; New York (State) -- Social life and customs; Rochester (N.Y.) -- Social life and customs; United States -- Politics and government -- 1845-1861.; Washington (D.C.) -- Description and travel; Washington (D.C.) -- Social life and customs; Horsford family